Under Five Nutritional Assessments in Selected Rural Areas of Chamarajanagara District with a View to Developing an Information Pamphlet - S, Usha N; M, Mahadevswamy K; G, Vinay Kumar (Research & Review: Management of Emergency and Trauma Nursing (e-ISSN: 2582-0494), 2023)
Background: Children are the most vulnerable group in any society, and nutritional status is the key indication of their health. Undernutrition results in severe emotional, mental, and bodily suffering. The Integrated Child Development Services programme, which includes Anganwadi, was established to fight child hunger and malnutrition (1). Malnutrition is a risk threatening vulnerable people due to multiple factors related to poverty and food security in the country in addition to the spread of diseases and several social factors that negatively affect the nutritional status of society. Objective: To assess the nutritional status of children under five and compare with WHO growth standards in Anganwadi in Alur, Chamarajanagara district. Methodology: An explorative descriptive method has been adopted and 61 children under five were selected for the study. Obtained data from questionnaires on demographic proforma, physical examination, and anthropometric measurements. Results: This study shows that 52.45% of children are according to weight for the age that is normal and 32.78% are wasted and 14.75% are severely wasted, 32.78% of children are according to height for the age is normal and 54.09% are stunted and 13.11% are severely stunted. 24.59% of children are normal according to BMI for age and 75.40% of children are stunted. Conclusion: There are numerous nutritional programmes existing for children to decrease the prevalence of malnutrition among them. The study concludes that 52.45% of children are according to weight for age, 32.78% of children are according to height for age and 24.59% of children according to their BMI for age, despite all the efforts by the government.